To solve the system of equations using substitution, we start with the two equations given:
- \( y = x^2 - x - 40 \)
- \( y = -3x - 5 \)
Since both equations equal \( y \), we can set them equal to each other:
\[ x^2 - x - 40 = -3x - 5 \]
Next, we will move all terms to one side to form a quadratic equation:
\[ x^2 - x + 3x - 40 + 5 = 0 \]
This simplifies to:
\[ x^2 + 2x - 35 = 0 \]
Now we factor the quadratic equation:
\[ (x + 7)(x - 5) = 0 \]
Setting each factor to zero gives us the solutions for \( x \):
- \( x + 7 = 0 \) → \( x = -7 \)
- \( x - 5 = 0 \) → \( x = 5 \)
Next, we substitute these \( x \)-values back into one of the original equations to find the corresponding \( y \)-values. We will use the second equation \( y = -3x - 5 \):
-
For \( x = -7 \): \[ y = -3(-7) - 5 = 21 - 5 = 16 \] So one solution is \( (-7, 16) \).
-
For \( x = 5 \): \[ y = -3(5) - 5 = -15 - 5 = -20 \] So the other solution is \( (5, -20) \).
Thus, the solutions to the system of equations are:
\((-7, 16)\) and \((5, -20)\).
Looking at the provided answer choices:
- (5,−20) and (−7,16) matches our solutions.
Therefore, the correct response is:
(5,−20) and (−7,16).